The effect of tooth shape ratio on mandibular incisors arrangement in Iraqi adult subjects - Sami K Al-Joubori; Mohammed Nahidh (College of Dentistry/ University of Baghdad, 2014)
Background: This study aimed to assess the effect of tooth shape ratio on mandibular incisor arrangement. Materials and methods: The sample included dental casts of some dental students and orthodontic patients having Class I dental and skeletal patterns with normal occlusion and severe crowding. The sample was divided into two groups according to the severity of crowding into: group I had Class I normal occlusion with mild or no crowded mandibular dentition and group II had Class I malocclusion with severe crowded mandibular dentition. Each group comprising of 40 subjects (20 males and 20 females). The mesio-distal and facio-lingual crown diameters were measured manually for each cast using modified vernier caliper gauge. Descriptive statistics were obtained for the measurements for both genders; independent samples t-test was performed to evaluate the gender difference in each group and to evaluate the groups' difference in total sample. Results and Conclusions: The results showed that there is non-significant genders difference in both groups. Generally, the mesio-distal and facio-lingual dimensions were higher in severely crowded mandibular incisor group. Neither facio-lingual dimension nor the tooth shape ratio has significant influence of the mandibular incisor arrangement and the mesio-distal dimension is the most important factor.